INTEGRATING THE SUSTAINABLE DEVELOPMENT GOALS (SDGS) INTO MAQASID AL-SHARI'A: A FRAMEWORK FOR MODERN ISLAMIC ECONOMIC LAW - Muh. Nur; Shahinur Rahman; Emma Clark; Mutiara M (Yayasan Adra Karima Hubbi, 2025)
The growing global emphasis on sustainable development has prompted renewed interest in aligning the United Nations’ Sustainable Development Goals (SDGs) with Islamic legal and ethical principles. This study explores the conceptual integration of the SDGs within the framework of Maqasid al-Shari‘a (the higher objectives of Islamic law), focusing on how Islamic economic law can operationalize sustainability through justice, equity, and human welfare. The research aims to construct a normative and practical framework that harmonizes the ethical imperatives of Maqasid al-Shari‘a with the multidimensional targets of the SDGs, particularly in areas of poverty alleviation, environmental protection, and social inclusion. A qualitative doctrinal approach is employed, combining textual analysis of classical Islamic legal sources with comparative evaluation of contemporary economic policies and global sustainability reports. The findings indicate that Maqasid al-Shari‘a naturally aligns with SDG principles through shared values such as preservation of life, intellect, wealth, lineage, and faith, forming a moral foundation for sustainable economic governance. The proposed framework demonstrates that integrating SDGs into Islamic legal thought can strengthen policy legitimacy, bridge ethical and developmental paradigms, and foster a holistic model for modern Islamic economic law.